Physician Perspectives on the Implementation of a Trauma-Informed Care Initiative in the Maternity Care Setting - Huartson, Karolina; Hill, Todd; Killam, Teresa; Kelly, Martina; Racine, Nicole (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objectives: To explore the barriers and facilitators from the perspective of family physicians on the implementation of a pilot trauma-informed care (TIC) initiative to promote resilience, with particular emphasis on asking about adverse childhood experiences (ACEs), in a maternity care clinic.